CTCF-activated FUCA1 functions as a tumor suppressor by promoting autophagy flux and serum α-L-fucosidase serves as a potential biomarker for prognosis in ccRCC - Shuo Zhao; Jiajia Sun; Qinzheng Chang; Shuo Pang; Nianzhao Zhang; Yidong Fan; Jikai Liu (Cancer Cell International, 2024)
Abstract Notably, clear cell renal cell carcinoma (ccRCC) is characterized by a distinct metabolic tumor phenotype that involves the reprogramming of multiple metabolic pathways. Although there is increasing evidence linking FUCA1 to malignancies, its specific role and downstream signaling pathways in ccRCC remain poorly understood. Here we found that FUCA1 expression was significantly downregulated in ccRCC tissues, which also predicts poor prognosis of ccRCCpatients. Moreover, enhancing FUCA1 expression resulted in reduced invasion and migration of ccRCC cells, further indicating its protective role. CHIP-qPCR and luciferase assays showed that CTCF was an upstream transcription factor of FUCA1 and could reverse the effects caused by FUCA1 inactivation. The change in FUCA1 led to changes in the results of various autophagy-related proteins and the mRFP-GFP-LC3 dual fluorescence system, indicating that it may play a role in the fusion stage of autophagy. Protein-protein interaction analysis revealed that FUCA2 exhibited the closest interaction with FUCA1 and strongly predicted the prognosis of ccRCC patients. Additionally, serum AFU encoded by FUCA2 could serve as a valuable predictor for survival in ccRCC patients. FUCA1 suppresses invasion and migration of ccRCC cells, with its activity being modulated by CTCF. FUCA1 regulates the autophagy process in ccRCC cells by influencing the fusion between autophagosomes and lysosomes. FUCA2 shares similarities with FUCA1, and elevated serum AFU levels along with increased expression of FUCA2 are indicative of a favorable prognosis in ccRCC.